2017
DOI: 10.3390/inorganics5020027
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Current Electrodeposition of Silicon Thin Films Anodes for Lithium Ion Battery Applications

Abstract: Electrodeposition of amorphous silicon thin films on Cu substrate from organic ionic electrolyte using pulsed electrodeposition conditions has been studied. Scanning electron microscopy analysis shows a drastic change in the morphology of these electrodeposited silicon thin films at different frequencies of 0, 500, 1000, and 5000 Hz studied due to the change in nucleation and the growth mechanisms. These electrodeposited films, when tested in a lithium ion battery configuration, showed improvement in stability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…However, commercialization of this amazing material is delayed by an unsolved issue of its significant volume expansion (up to 280 %) during the electrochemical reaction with lithium and the formation of lithiated Li 3.75 Si alloy. The mechanical stress occurring during alloying leads to degradation, cracking, and electrical contact loss in the electrode . Another resulting issue of Si expansion is the formation of a non‐uniform thick solid electrolyte interphase (SEI), which obstructs the movement of Li + ions, leading to capacity fading .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, commercialization of this amazing material is delayed by an unsolved issue of its significant volume expansion (up to 280 %) during the electrochemical reaction with lithium and the formation of lithiated Li 3.75 Si alloy. The mechanical stress occurring during alloying leads to degradation, cracking, and electrical contact loss in the electrode . Another resulting issue of Si expansion is the formation of a non‐uniform thick solid electrolyte interphase (SEI), which obstructs the movement of Li + ions, leading to capacity fading .…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that the decrease of Si particle size to the nanoscale prevents the cracking of particles . Amorphous phase Si (a‐Si) has been found to be preferable over crystalline Si, because it experiences uniform expansion during the repetitive lithiation/delilthiation reaction and mitigates the cracking of Si particles . Incorporation of dopants, especially n‐type dopants, into Si materials leads to enhanced electron mobility .…”
Section: Introductionmentioning
confidence: 99%
“…40 However, silicon films deposited from organic electrolytes are often considered as anode material. 42,43 Information on the electrochemical properties of silicon materials synthesized from fluoridecontaining melts is poorly presented in the literature, 22,44 nevertheless there are many papers focused on synthesis alone. 45 The advantages of chloride melts with low fluorine content include the low cost and high purity of reagents, low solubility of oxides, and also the non-hygroscopic nature of the system.…”
mentioning
confidence: 99%